Die kognitive Dimension des Kreuzes Zur Deutung des Todes Jesu im Johannesevangelium - Nielsen, Jesper Tang (Mohr Siebeck, 2009)
The Cognitive Dimension of the Cross. The Interpretation of Jesus Death in the Fourth Gospel.
PublicationDate: 20090622
Keywords: Johannesevangelium -- Tod Jesu -- Narratologie -- Semiotik -- Neues Testament -- Array